Analisis Fluktuasi Harga Emas dan Tingkat Inflasi terhadap Pendapatan Gadai Emas Syariah di Bank Syariah Mandiri - Zalpa Salsabila Putri; Nur'aeni Nur'aeni (Indonesian Journal of Economics and Management, 2021)
The purpose of this study is to explore the effect of gold price fluctuations and inflation rates on sharia gold pawn Income at Bank Syariah Mandiri. The data used is the annual published financial report of Bank Syariah Mandiri for the period 2016 to 2020. For the data analysis technique, multiple linear regression is used in each model, namely Bank Mandiri Syariah. The results of the study show that a) Gold price fluctuations have a positive and significant effect on sharia gold pawn income, b) Inflation rate has a positive and significant effect on sharia gold pawn income, and gold price fluctuations and inflation rates simultaneously have a significant effect on sharia gold pawn income.